Equi-biaxial fatigue testing of EPM utilising bubble inflation. (August 2016) - Johnson, Mark; Murphy, Niall; Ekins, Ray; Hanley, John; Jerrams, Stephen
Abstract: This paper describes an equi-biaxial tension fatigue test system which utilises the bubble inflation method to subject elastomers to equi-biaxial fatigue loading between user-defined limits of pressure, volume, stretch ratio or stress. The test system integrates a hydraulic inflation system, a high speed vision system and a control system. The high-speed vision system allows the stretch ratio and stress acting on the test specimen to be evaluated in real-time during testing. This in turn allows either stretch ratio or stress to be used as a direct control limit. In this research, constant maximum engineering stress control tests have been carried out to evaluate the suitability of the developed dynamic bubble inflation system for equi-biaxial fatigue testing of elastomers. The resulting test data was used to produce Wöhler (S/N) curves and stress/stretch ratio plots for ethylene-propylene rubber (EPM).